2003
DOI: 10.1073/pnas.1334098100
|View full text |Cite
|
Sign up to set email alerts
|

Divergent impact of progesterone and medroxyprogesterone acetate (Provera) on nuclear mitogen-activated protein kinase signaling

Abstract: The impact of progestins on estrogen-inducible mechanisms of neuroprotection was investigated. Previously, we showed that estrogen and progesterone are neuroprotective against excitotoxicity, whereas the synthetic progestin medroxyprogesterone acetate (MPA; Provera) is not. Here, we demonstrate that 17␤-estradiol (E 2) and progesterone (P4) treatment of hippocampal neurons attenuated the excitotoxic glutamate-induced rise in intracellular calcium concentration. Although MPA had no effect alone, MPA completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
158
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(176 citation statements)
references
References 43 publications
16
158
1
1
Order By: Relevance
“…The intensity of pERK1/2 signal increased gradually from 10 to 30 min with a time-dependent increase. We further observed that E 2 induced pERK translocation to the nucleus, which was consistent with previous observations from our group (Nilsen and Brinton, 2003b). Nuclear localization of pERK1/2, which was evident at the first time point of 10 min, was sustained at 20 and 30 min.…”
Section: E 2 Increased Akt and Erk1/2 Phosphorylation In A Time-depensupporting
confidence: 93%
See 3 more Smart Citations
“…The intensity of pERK1/2 signal increased gradually from 10 to 30 min with a time-dependent increase. We further observed that E 2 induced pERK translocation to the nucleus, which was consistent with previous observations from our group (Nilsen and Brinton, 2003b). Nuclear localization of pERK1/2, which was evident at the first time point of 10 min, was sustained at 20 and 30 min.…”
Section: E 2 Increased Akt and Erk1/2 Phosphorylation In A Time-depensupporting
confidence: 93%
“…Primary cultures of cortical neurons were obtained from embryonic day 18 rat fetuses as described previously (Nilsen and Brinton, 2003b;Brewer et al, 2006). Briefly, cortical cells were dissected and treated with 0.02% trypsin in HBSS (Invitrogen) for 5 min at 37°C and dissociated by repeated passage through a series of fire-polished constricted Pasteur pipettes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some model systems, progestogens such as medroxyprogesterone acetate (MPA) are associated with outcomes very different from those associated with progesterone (Nilsen and Brinton 2003). At the same time, there is increasing evidence that progesterone has neuroprotective effects that may be very useful clinically (Stein 2007).…”
Section: Basic Science Studiesmentioning
confidence: 99%